TINJAUAN KELENGKAPAN PENGISIAN FORMULIR CPPT RAWAT INAP DENGAN KETEPATAN DIAGNOSIS PENYKIT BERDASARKAN ICD-10 DI RSJ. HB. SAANIN PADANG TAHUN 2022 - Indra, Indra; Yulia, Yulfa; Wirman, Wirman (Ensiklopedia of Journal, 2022)
The incompleteness of filling out the inpatient Integrated Patient Progress Record (CPPT) form can affect the accuracy of disease diagnosis coding. Based on the results of the initial survey on 10 inpatient medical records, 7(70%) CPPT incompleteness and 4(40%) inaccuracy in coding disease diagnosis. The purpose of this study was to determine the relationship between the completeness of filling out the inpatient CPPT form with the accuracy of coding a disease diagnosis based on ICD-10 at Prof. Mental Hospital. HB. Saanin Padang. This research is descriptive correlational with quantitative. The research was carried out at the Prof. Mental Hospital. HB. Saanin Padang on June 13-17, 2022. The population in this study was medical records of inpatients in April 2022 as many as 223 medical records with a sample of 69 medical records and sampling using simple random sampling. Data was collected by observation and data processing techniques of editing, coding, tabulating, and cleaning. The analysis used is univariate analysis and bivariate analysis. The results of the study showed that 67(97.1%) incomplete inpatient CPPT forms were filled in, 5(7.2%). filling in the CPPT with the accuracy of coding the diagnosis of disease with value=1,000(P>0.05). The conclusion of the study that there is no significant relationship between the completeness of filling the CPPT with the accuracy of coding the diagnosis of disease, but the incompleteness of filling in the CPPT inpatients is still in the high category, it is recommended to Professional Care Providers (PPA) to fill out the CPPT completely.Keywords: CPPT, ICD-10, completeness, coding accuracy